A new species of hypodematium (hypodematiaceae) From CHINA (Bangladesh Journal of Botany, 2023)
Hypodematium chingii J. X. Li & X. J. Li, sp. nov., a new species of Hypodematium Kunze belonging to Hypodematiaceae from Yinan County, Linyi City, China is described and illustrated. It is closer to H. sinense K. Iwats and H. fordii (Baker) Ching but differs by its stipe sparsely rod-shaped glandular hairs, triangular laminae, sparsely covered indusia with short acicular and glandular hairs, tuberculate perispore with protrusions, and surface with scaly ornamentation. Results of comprehensive studies on morphological, anatomy and Scanning Electron Microscopy (SEM) of these three species are presented, and SEM structures of laminae and spores are provided. A key to the closely related species is also presented.Bangladesh J. Bot. 52(2): 631-638, 2023 (June) Special